2015
DOI: 10.1177/0264619615571138
|View full text |Cite
|
Sign up to set email alerts
|

Looking back at the service delivery models of sex education in the United States: Adults with visual impairments report on their experiences

Abstract: This study investigated the sex education experiences of adults with visual impairments who attended either an itinerant or residential service delivery model during their school age years in the United States. We sought to answer the research questions through an online survey instrument that included quantifiable survey items. Findings demonstrate particular sex education content presented to participants in the school curriculum was more frequent for participants who attended residential schools. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The researchers concluded that, students learned through methods that were outside schools (Wild et al, 2014). In addition, Kelly et al (2015) pointed that, using the new materials and methods such as; role plays, explicit talk, tactile graphics, electronic materials, anatomically correct models can be used for sex education in adults with visually impartment.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers concluded that, students learned through methods that were outside schools (Wild et al, 2014). In addition, Kelly et al (2015) pointed that, using the new materials and methods such as; role plays, explicit talk, tactile graphics, electronic materials, anatomically correct models can be used for sex education in adults with visually impartment.…”
Section: Discussionmentioning
confidence: 99%